Distributary development in a 21st century river: The evolution of Neptune Pass and its delta, the largest new offshoot of the Mississippi River - Alexander S. Kolker; H. Dallon Weathers; Christy Swann; Alisha A. Renfro (PLoS ONE, 2025)
The development of distributaries in large river deltas plays an important role in the geology, hydrology, and ecology of the coastal ocean, as large rivers are a dominant mechanism by which particulate, suspended, and dissolved material is delivered from the continents to the global ocean. And yet, there is relatively little, near-real time observational data on the development of distributaries in large river deltas -- in part because the development of modern observation coincides with an era when rivers have been controlled by large engineering projects (i.e., the 20th and 21st centuries). This article reports on Neptune Pass, the largest new distributary to form in the Mississippi River in nearly a century. It developed between 2019 and 2021 when a small canal rapidly expanded by at least an order of magnitude. The system now carries about 15–17% of the flow of the Mississippi River, > 3,000 m3 s-1 when the Mississippi River is at moderately high flows. This is comparable to the 10th largest river in North America and the 100th largest river on Earth. Neptune Pass is building a delta, and this study sought to examine whether this delta is comprised largely of material eroded from the Neptune Pass (redistributed sediment hypothesis), or includes material recently derived from the Mississippi River (new sediment hypothesis). These hypotheses were tested using a combination of marine-geophysical surveys, remote sensing techniques, and sediment core collections. Results indicate that the delta in Quarantine Bay was 56–79% larger than the material excavated from Neptune Pass, corroborating the new sediment hypothesis, and indicating that it is a net land building system. These findings provide key insights that are critical to the restoration and safe management of the Mississippi River and its delta, the largest system of its kind in North America.